Influence of cryoprecipitate, Factor XIII, and fibrinogen concentrate on hyperfibrinolysis. Issue 10 (21st July 2017) - Cushing, Melissa M.; Fitzgerald, Meghann M.; Harris, Rebecca M.; Asmis, Lars M.; Haas, Thorsten
Abstract : BACKGROUND: Hyperfibrinolysis is a potentially life‐threatening condition associated with poor clot integrity and excessive bleeding. Although antifibrinolytics are an effective treatment, more liberal use of these drugs may lead to a prothrombotic risk, and an earlier and potentially safer treatment option would be desirable. Hyperfibrinolysis has been shown to be attenuated by in vitro supplementation of purified human Factor (F)XIII concentrate. Cryoprecipitate represents an alternative source of FXIII and the only approved source of concentrated FXIII in some countries. The aim of this study was to investigate whether cryoprecipitate, FXIII, and fibrinogen concentrate mitigate hyperfibrinolysis. STUDY DESIGN AND METHODS: Ten citrate blood specimens from healthy subjects were spiked with tissue plasminogen activator (t‐PA) and subsequently supplemented with cryoprecipitate, FXIII, fibrinogen concentrate, and ɛ‐aminocaproic acid (EACA). Thromboelastometry tests were performed at baseline, after t‐PA, and after supplementation. Hyperfibrinolysis was assessed using the clot lysis index at 60 minutes (LI60; reciprocal of maximum lysis). RESULTS: The LI60 was significantly improved (fibrinolysis attenuated) after cryoprecipitate supplementation compared to t‐PA alone and compared to FXIII and fibrinogen concentrate. Hyperfibrinolysis was only fully reversed using EACA. In addition, cryoprecipitate demonstrated the least variability in the attenuation of hyperfibrinolysis among 10 healthy subjects, compared to FXIII and fibrinogen concentrate. CONCLUSION: This is the first study to show that cryoprecipitate is able to significantly mitigate hyperfibrinolysis in an in vitro model. Further investigations are warranted to determine whether cryoprecipitate may have a previously unrecognized benefit and should be administered earlier in resuscitation protocols.